Determinants of water connection type and ownership of water-using applianes in Ireland - Joe O'Doherty; Seán Lyons; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2007)
Domestic water demand is influenced both by the number of households and their characteristics, in particular the extent to which they employ water-using appliances. This paper focuses on domestic ownership of water-using appliances in Ireland, a country where rapid economic and demographic change are putting pressure on water and sewerage infrastructure. Using a large household micro-dataset, we use discrete response logistic models to examine the determinants of the water and sewage mains connection status of Irish homes, identify the characteristics of households that are associated with having larger or smaller numbers of appliances, and investigate what types of households own particular combinations of appliances.
Keywords: 330; Water usage; Ireland; appliance ownership; water supply; Wasserversorgung; Konsumentenverhalten; Privater Haushalt; Schätzung; Irland